Towards a biological monitoring guidance value for acrylamide. Issue 1 (19th August 2015) - Sams, C.; Jones, K.; Warren, N.; Cocker, J.; Bell, S.; Bull, P.; Cain, M.
Highlights We report a study of workers at a UK acrylamide production plant. Biological monitoring data (urine metabolites and haemoglobin adducts) are given. Their relationship with environmental (air and hand wash) levels were investigated. We propose urinary acrylamide-mercapturic acid as the preferred biomarker. A guidance value is proposed.